Gambaran Pengetahuan Tentang Sadari Pada Murid Kelas XI SMA Negeri 1 Kadugede Kecamatan Kadugede Kabupaten Kuningan - Kurniasih, Nita Ike Dwi; Srimulyawati, Tia; Asrina, A (JURNAL KESEHATAN TERAPAN, 2023)
Sadari is a breast self examination which aimed at early detection of an abnormal lump in SADARI is an examination of the breast itself whose aim is to detect early the presence of abnormal lumps in the breast, detect early the presence of abnormal lumps in the breast to detect early the presence of cancer. The main indication for BSE is a diagnosis of breast cancer from the front, left and right and paying attention to whether there are lumps, changes in skin color, scaly nipples, fluid or pus discharge and blood detection. The aim of this research is to determine the description of knowledge about BSE in Class XI Students of SMA Negeri 1 Kadugede, Kadugede District, Kuningan Regency. This research uses a Descriptive Survey method which aims to see a picture of female students' knowledge about Awareness. The research population was all students of SMA Negeri 1 Kadugede in 2023. Primary data was obtained through direct interviews with all class XI students of SMA Negeri 1 Kadugede using a questionnaire. This data was analyzed univariately using a descriptive survey method which aims to obtain an overall picture of students' knowledge and attitudes towards BSE in 2023 at SMA Negri 1 Kadugede. Univariate analysis was carried out using research outcome variables. This analysis only provides the distribution and percentage of each variable. Based on research results, good knowledge in Class , Knowledge about prevention by implementing BSE is 75%